Evaluation of the Expression and Function of the TRE2-like and TRE2 Genes in Ecdysis of Harmonia axyridis - Li, Yan; Chen, Xu; Wang, Sha-Sha; Pan, Bi-Ying; Wang, Shi-Gui; Wang, Su; Tang, Bin (Frontiers in Physiology, 2019)
Harmonia axyridis is an important predatory natural enemy insect, and widely used in biological control of agricultural and forestry pests. Trehalose is directly involved in the energy storage of the H. axyridis and the oxidative function of various physiological activities, providing an energy source for its growth and development. The aim of this study was to explore the potential role of membrane-bound-like trehalase (TRE2-like) and membrane-bound trehalase (TRE2) genes in H. axyridis by RNA interference (RNAi) silencing of TRE2-like and TRE2 genes analysis. In addition, we further determined the activity of soluble and membrane-bound trehalase, the expression of trehalose metabolism and glycogen metabolism related genes in TRE2-like or TRE2 RNAi larvae. The results showed that some adults wing abnormality and death, trehalase activity, trehalose content, the expression of glycogen metabolism-related genes and chitin pathway genes were also affected after TRE2-like and TRE2 RNAi. These study indicated that RNA interference is capable of reducing gene expression of TRE2-like and TRE2, thereby disrupting trehalose metabolism which in turn affects the chitin synthesis pathway and also leads to developmental defects like wing deformities. This study provides some theoretical guidance for the function of TRE2 gene in other insects.